Adaptive Business Model in the Post-Pandemic Era of Covid-19: Evidence in Greensa Inn - Yudha, Ana Toni Roby Candra; Basya, Maziyah Mazza (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The aims of this study are to examine and obtain an adaptive business model for the GreenSA Inn hotel business in the form of meetings, intensive, conferences, and exhibitions (MICE). The research method used is a mixed method, namely by using SWOT analysis as a representation of the analytical tool in the quantitative approach, followed by observation and in-depth interviews as a representation of the qualitative approach. There were 7 selected informants who held positions at the level of directors or coordinators and technical implementers. The results obtained by the strategy model are aggressive strategies, namely with a business expansion strategy that focuses on efforts to 'pick up the ball' utilizing all advantages possessed. First, the uniqueness of this study is that it identifies one business area and business unit, namely MICE, so the review is quite detailed but cannot be generalized. Recommendations that are consistent with the study results are promoting marketing channels through social media, and collaborating with religious institutions at the Sidoarjo and Surabaya district levels to offer external meeting activities at GreenSA. Then to be able to obtain a more effective adaptive strategy, a ghost shopper can be carried out at hotels in other districts or other campuses to get information and references for the adaptive strategies they are working on.